From Protection to Vigilance: A Narrative Study of Policing, Race, and Mental Health in the Life of a Black Man - Shane King (Journal of Behavioral Health and Psychology, 2026)
This study uses narrative inquiry to explore how a Black man from a marginalized community makes sense of repeated encounters with law enforcement throughout his life. Guided by the social-ecological framework and informed by research on structural racism and race-based trauma, it examines how experiences such as racial profiling, traffic stops, and police misconduct affect trust, safety, and perceptions of legitimacy. The narrative analysis traces the timeline of these experiences, key turning points, and the meaning attributed to police interactions over time. Results indicate that early views of police as protectors gradually changed into caution, hypervigilance, and distrust after repeated perceived unjust encounters. Instead of being isolated events, these interactions became part of the participant's understanding of safety, self-protection, and his relationship with law enforcement. The study adds to social work scholarship by showing how policing experiences can serve as an ongoing social determinant of mental health and influence identity, behavior, and trust in institutions among men of color in marginalized communities.